The Managerial Challenge of Comparable Job Worth and Job Evaluation - Déom, Esther (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "The Managerial Challenge of Comparable Job Worth and Job Evaluation," by Thomas J. Patten.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z